Vander's human physiology : the mechanisms of body function - Widmaier, Eric P; Raff, Hershel, 1953-; Strang, Kevin T (Boston : McGraw-Hill, 2006)
Present the fundamental principles and facts of human physiology in a format that is suitable for undergraduate students regardless of academic backgrounds or fields of study. The most significant feature of this text is its clear and accurate descriptions of mechanisms, rather than mere descriptions of facts and events. As evidence, the book employs numerous flow diagrams that illustrate clearly defined chains of casual links. The text's theme reflects the dominant theme of human physiology; homeostasis. Each body system is approached from the vantage point of homeostasis as achieved through the coordinated functions of homeostatic control systems
Homeostasis: a framework for human physiology -- Chemical composition of the body -- Cell structure and protein function -- Movement of molecules across cell membranes -- Control of cells by chemical messengers -- Neuronal signaling and the structure of the nervous system -- Sensory physiology -- Consciousness, the brain, and behavior -- Muscle -- Control of body movement -- Endocrine system -- Cardiovascular physiology -- Respiratory physiology -- Kidneys and regulation of water and inorganic ions -- Digestion and absorption of food -- Regulation of organic metabolism and energy balance -- Reproduction -- Defense mechanisms of the body
Includes bibliographical references (page 799) and index
Keywords: Human physiology; Physiology